Knowledge and Readiness to Adopt Green Computing Practices Among Librarians and Academic Staff in a Private University in Delta State, Nigeria - Ivwighreghweta, Oghenetega; Adjogri, Kelvin Dawandakpoye Onajite (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
This study investigated the knowledge and readiness of librarians and academic staff in private universities in Delta State, Nigeria, to adopt green computing practices. It aimed to assess their awareness levels, knowledge of green computing practices, and willingness to implement them. Using a descriptive survey research design, data was collected from 185 librarians and academic staff across Western Delta University, Oghara, and Michael and Cecilia Ibru University through questionnaires. The analysis was conducted using frequency and percentage. The study revealed that a significant number of respondents were unaware of green computing concepts and practices. However, despite this lack of awareness, they demonstrated a willingness to adopt green computing practices within their institutions. Based on these findings, the researchers recommended that university management should organize workshops, orientations, and seminars to educate librarians, academic staff, and other computer users on green computing, particularly focusing on proper disposal and recycling of computer hardware. Additionally, the National Universities Commission (NUC) should establish and enforce a green computing policy across Nigerian universities to promote sustainable computing practices. Implementing these recommendations will help bridge the knowledge gap and encourage environmentally friendly computing behaviours’ in academic institutions.